2020
DOI: 10.1177/1465312520910755
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of accuracy of mesiodistal tooth measurements made in conventional study models and digital models obtained from intraoral scan and desktop scan of study models

Abstract: Objective: To compare the measured values obtained from the plaster model, digital models created by scanning the plaster models and direct intraoral scanning with the values obtained from direct intraoral measurements. Design: This was a prospective clinical study. Setting: The study was conducted in Department of Orthodontics, Saveetha Dental College and Hospital, Tamil Nadu, India. Participants: Ten patients before the start of orthodontic treatment were selected for the study. Methods: A computer-aided des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The accuracy of the calibrated digital model measuring tool of the Ortho Analyzer software has been investigated, and its reliability and precision were confirmed [ 33 ]. More recently, intraoral direct measurements taken in individuals’ oral cavity with a 0.01-mm accuracy digital caliper were compared to measurements using the 3 Shape Ortho Analyzer cross-sectional tool; results indicated that these measurements are accurate replica and as reliable as direct measurements [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the calibrated digital model measuring tool of the Ortho Analyzer software has been investigated, and its reliability and precision were confirmed [ 33 ]. More recently, intraoral direct measurements taken in individuals’ oral cavity with a 0.01-mm accuracy digital caliper were compared to measurements using the 3 Shape Ortho Analyzer cross-sectional tool; results indicated that these measurements are accurate replica and as reliable as direct measurements [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A better approach would have been to make digital impressions, but an intra-oral scanner wasn't available in the practice at the time of the study. The direct digitization of the dentition by means of an intra-oral scanner is at least as accurate as the indirect digitization of gypsum study casts using a lab scanner [66,67]. The use of an intra-oral scanner could have improved the precision and would have simplified the protocol [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Tooth size measurements were performed directly on dental casts using digital calipers, except for ( Alshahrani et al, 2020 ) and ( Al Sulaimani and Afify, 2006 ), who scanned the models and performed measurements using a computer software. Both measurement methods have been tested for accuracy by many authors, who reported no significant difference between the two methods ( Abuhassan and Asiry, 2021 , Amuk et al, 2019 , Murugesan and Sivakumar, 2020 ).…”
Section: Discussionmentioning
confidence: 99%